Research on the longitudinal movement and influence of restraint parameters of the long-span suspension bridge’s main girder - Hongbin, Sun; Jieyi, Yuan; Yujing, Liu (Frontiers in Materials, 2023)
The long-span suspension bridge has suffered from multiple failures of restraints such as supports, dampers, and expansion joints due to excessive accumulated displacement at the girder end. To investigate the main girders' characteristics in the longitudinal motion of these bridges and the influence of the restraint device on the longitudinal displacement, the motion characteristics were first analyzed based on the measured displacement data of a certain bridge's main girder; a dynamic finite element model of the bridge's random traffic flow was then established based on the measured WIM data; combined with the girder end displacement monitoring data, the Euclidean distance was used to verify the correctness and rationality of the proposed model; finally, the model is used to discuss the influence of restraint devices (i.e. viscous dampers and supports) on the main girder in the longitudinal direction. The results show that dynamic loads (such as vehicles and wind) are the principal reasons for huge accumulated travel at the girder end; The viscous damper can effectively control the longitudinal movement; in a certain range, the larger the damping index, the better the control effect of the damper; meanwhile, the friction coefficient of the support also affects the longitudinal motion, but the effect is limited. When the friction coefficient is≤0.03, the girder end's cumulative displacement gradually decreases with the increasing friction coefficient, and compared to the damping index, the friction coefficient plays a major controlling role in the girder end displacement; when the friction coefficient is > 0.03, the damping index plays a major controlling role in the girder end displacement.